Prognostic value of CD4+ in patients with Т1–2N0M0 breast cancer - R. M. Paltuev; A. G. Kudaybergenova; V. F. Semiglazov; A. V. Komyakhov; A. I. Tseluyko (Опухоли женской репродуктивной системы, 2023)
Aim. To evaluate the prognostic value of CD4+ in patients with T1–2N0M0 breast cancer.Materials and methods. We performed a quantitative assessment of CD4+ T-lymphocytes in tumor stromal cells and determined the prognostic parameter using the method developed by us (patent No. RU2697709C1 dated 19.08.2019) in 394 patients diagnosed with infiltrative breast cancer. Survival of patients in the analyzed group was assessed over a period of 10 years.Archival material from paraffin blocks of the «target group» was used in the work for molecular genetic profiling techniques (T1–2N0M0, 1118 patients, 2000–2009). A histological preparation stained with hematoxylin and eosin was scanned, and the central and peripheral zones of the tumor were isolated. To identify CD4+ T-lymphocytes, the immunohistochemical study of preparations obtained with rabbit anti-CD4 monoclonal antibodies was performed. After rescanning histological and immunohistochemical preparations, combining different immunohistochemical stains, the cell density in the tumor and stromal components was calculated in preparations stained with hematoxylin and eosin and CD4. For further calculations, we used the data obtained as a result of the number of stromal cells reduced to 1 mm2 (according to the preparation stained with hematoxylin and eosin), the so-called cell density per calculated number of CD4+-stained cells (cell area × proportion of CD4+ cells in percentages). The resulting ratio is used to predict the outcome of breast cancer: if its value is ≤ 50 %, the prognosis is assessed as favorable (in which the patient’s survival is 10 years or more).Results. In 296 (75 %) of 394 observed patients, the proportion of CD4+ T-lymphocytes in tumor stromal cells was ≤ 50 %. Over 10 years, the overall survival of patients in this group was 93 %, which is considered a statistically favorable group for breast cancer (stages T1–2, N0). In 98 (25 %) of 394 observed patients, the proportion of CD4+ T-lymphocytes in tumor stromal cells was ˃50 %. Over 10 years, the overall survival of patients in this group was 82 %, which is considered a statistically unfavorable group for breast cancer (stages T1–2, N0).Conclusion. Our findings suggest high accuracy of our method of breast cancer prognosis based on the quantitative assessment of CD4+ T-lymphocytes in tumor stromal cells. It can be used for breast cancer prognosis in early stages (T1–2, N0).